2020
DOI: 10.1177/016146812012200910
|View full text |Cite
|
Sign up to set email alerts
|

Equity Advocates Using Equity-Mindedness to Interrupt Faculty Hiring's Racial Structure

Abstract: Background/Context Education scholars have recommended steps for college and university leaders to take toward creating a more racially diverse professoriate. However, the majority of the scholarship is neither empirical nor focused on faculty actively negotiating barriers during search committee meetings to create equitable practices. Purpose/Objective/Research Question/Focus of Study The study examined faculty within search committees who received formal training to interrogate exclusionary hiring procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Search members believed they were operating based on merit and objectivity, when in fact, they were perpetuating gendered, racialized, and privileged forms of language, behaviors, and interactions with diverse candidates. While Tierney and Bensimon’s study was more than two decades ago, a recent study examining faculty searches through a racial lens revealed a similar account (Liera, 2020a). Liera found, however, that when search members intentionally critiqued the racialized roots of the academic search process, they were more apt to ensure equity in their hiring decisions.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Search members believed they were operating based on merit and objectivity, when in fact, they were perpetuating gendered, racialized, and privileged forms of language, behaviors, and interactions with diverse candidates. While Tierney and Bensimon’s study was more than two decades ago, a recent study examining faculty searches through a racial lens revealed a similar account (Liera, 2020a). Liera found, however, that when search members intentionally critiqued the racialized roots of the academic search process, they were more apt to ensure equity in their hiring decisions.…”
Section: Discussionmentioning
confidence: 93%
“…Faculty have been socialized to reproduce the normative faculty hierarchy of the institution in their institutional roles, which promotes a racialized organizational culture that privileges White culture (Bess & Dee, 2008;Liera, 2020aLiera, , 2020bTierney & Bensimon, 1996). Because they must operate in this interlocking network, they may not be well suited to challenge or see issues within the hierarchical, hegemonic, and biased structure of the university while serving in their dual role as a search chair and faculty member.…”
Section: The Role Of Race In Faculty Searchesmentioning
confidence: 99%
See 2 more Smart Citations
“…Internal and external pressures from various stakeholders have compelled institutional leaders to grapple with historic and contemporary racial disparities. This is especially true of the professoriate (e.g., Liera, 2020a , b ; White-Lewis, 2020 , 2021 ), yet concerns in this area are not merely isolated to matters of representation. The COVID-19 pandemic has exposed deeply intractable inequities in health, wealth, public policy, and technology that negatively impact racially minoritized students’ 1 educational opportunities ( Laster Pirtle, 2020 ).…”
Section: Introductionmentioning
confidence: 99%